Identification of novel 2-aminothiazole conjugated nitrofuran as antitubercular and antibacterial agents. Issue 15 (1st August 2016) - Ran, Kai; Gao, Chao; Deng, Hongxia; Lei, Qian; You, Xinyu; Wang, Ningyu; Shi, Yaojie; Liu, Zhihao; Wei, Wei; Peng, Cuiting; Xiong, Lu; Xiao, Kunjie; et al.
Graphical abstract: Abstract: The emergence of antibiotic resistant pathogens is an ongoing main problem in the therapy of bacterial infections. In order to develop promising antitubercular and antibacterial lead compounds, we designed and synthesized a new series of derivatives of 2-aminothiazole conjugated nitrofuran with activities against both Mycobacterium tuberculosis and Staphylococcus aureus . Eight compounds12e, 12k, 12l, 12m, 18a, 18d, 18e, and18j emerged as promising antitubercular agents. Structure–activity relationships (SARs) were discussed and showed that the derivatives substituted at the position-3 of benzene of 5-nitro- N -(4-phenylthiazol-2-yl)furan-2-carboxamide exhibited superior potency. The most potent compound18e, substituted with benzamide at this position, displayed minimum inhibitory concentrations (MICs) of 0.27 μg/mL against Mtb H37Ra and 1.36 μg/mL against S. aureus . Furthermore, compound18e had no obvious cytotoxicity to normal Vero cells (IC50 = 50.2 μM). The results suggest that the novel scaffolds of aminothiazole conjugated nitrofuran would be a promising class of potent antitubercular and antimicrobial agents.